2018
DOI: 10.1186/s12964-018-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the master regulator FOXM1 in cancer

Abstract: FOXM1 (forkhead box protein M1) is a critical proliferation-associated transcription factor that is widely spatiotemporally expressed during the cell cycle. It is closely involved with the processes of cell proliferation, self-renewal, and tumorigenesis. In most human cancers, FOXM1 is overexpressed, and this indicates a poor prognosis for cancer patients. FOXM1 maintains cancer hallmarks by regulating the expression of target genes at the transcriptional level. Due to its potential role as molecular target in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
290
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(299 citation statements)
references
References 137 publications
8
290
0
1
Order By: Relevance
“…Our previous report supported the opposite finding, ie, that BrdU-LIs did not increase in the residual kidneys of adult male rats after UNx (Matsushita et al, 2015). This inconsis- including kidney tumor cells (Kalin, Ustiyan, & Kalinichenko, 2011;Liang et al, 2018;Liao et al, 2018;Zhao et al, 2018). FOXM1 plays critical roles in cell division of these cells, and FOXM1-mediated cell F I G U R E 1 Cell proliferative activities in the residual kidneys of rats after unilateral nephrectomy (UNx).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our previous report supported the opposite finding, ie, that BrdU-LIs did not increase in the residual kidneys of adult male rats after UNx (Matsushita et al, 2015). This inconsis- including kidney tumor cells (Kalin, Ustiyan, & Kalinichenko, 2011;Liang et al, 2018;Liao et al, 2018;Zhao et al, 2018). FOXM1 plays critical roles in cell division of these cells, and FOXM1-mediated cell F I G U R E 1 Cell proliferative activities in the residual kidneys of rats after unilateral nephrectomy (UNx).…”
Section: Discussionsupporting
confidence: 66%
“…Canonical pathways related to the cell cycle were activated by UNx in both male and female rats cycle progression is involved in the G 1 /S and G 2 /M transitions (Halasi & Gartel, 2013;Kalin et al, 2011;Saldivar et al, 2018). (Liao et al, 2018). Therefore, we performed comprehensive analysis of miRNA expression, followed by mRNA/miRNA integrated analysis to investigate the detailed mechanisms of FOXM1 regulation in compensation in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Also, SETD3 methylates FoxM1 and negatively regulates the expression of Vascular Endothelial Growth Factor (VEGF) under normoxia conditions 21 , a known factor related to angiogenesis and tumor progression 58 . On the other hand, FoxM1 has an important role in cancer because its overexpression has been found to be related to poor prognosis in patients 29 . In our study, we found that the expression of FoxM1 also correlated with worse RFS in breast cancer patients ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In ATRT, studies have identified a population of cells expressing CD133 with cancer stem cell-like properties that are also resistant to ionizing radiation and have increased radiosensitivity [41,42]. FOXM1 is also closely tied to cancer cell stem cell properties such as cell proliferation, self-renewal, and tumorigenesis [62][63][64][65][66]. In glioblastoma, inhibition of FOXM1 sensitized tumors to irradiation in vitro and in vivo [67].…”
Section: Discussionmentioning
confidence: 99%